Controversies and New Hypotheses on Exercise-Induced Bronchospasm in Hot and Humid Air - Messan, Folly (My University, 2019)
Abstract—Bronchospasm is a chronic disease that affects the respiratory airways in both general and sporting populations. Bronchospasm has been mainly studied and documented extensively in athletes in continental climates of cold and dry air. The prevalence values observed for this disease were increased in these athletes. On the other hand, the prevalence declined among athletes acclimated to the hot and humid air climate. As a result, the quality of inhaled ambient air appears to be a determining factor in the pathophysiology of bronchospasm. Thus, in recent years, there has been controversy concerning the role of warm moist air in exacerbating or alleviating bronchospasm. Previous studies have suggested that the high temperature of inhaled air during physical exertion is an explanation for the low prevalence values. However, studies performed in tropical areas highlight the high prevalence values of bronchospasm. This review is based on explanatory hypotheses related to changes in airflow and the effects of heat exchange and freshness on the epithelium. Finally, the induced effects are addressed under conditions where the temperature of the inhaled ambient air is lower or higher than that of the body fixed at 37 °C. On the basis of the assumptions made in this review, we suggest that exercise-induced bronchospasm in athletes is just as important in hot and humid air conditions as it is in cold and dry air conditions. The variability in the prevalence values of bronchospasm on which the controversies are based is mainly due to different states of training of the subjects, the nature and intensity of the effort, the various parameters and diagnostic criteria of the sportsmen, and assessments of bronchospasm and different modes of breathing. We hypothesized that in cold and dry air environments, the small lower airways of athletes are more vulnerable than those of their counterparts to pathophysiology in hot and humid climates. Professional sportsmen who specialize in long-distance endurance sports therefore truly expose their small airways to various pathologies
Keywords: Exercise-induced bronchospasm; Controversy; Hypothesis; Hot and humid air